Regulation of protein metabolism in cancer - Cecil Han; Xiongbin Lu; Deepak Nagrath (Molecular & Cellular Oncology, 2018)
Our recent studies determined molecular interactions between genes in the ubiquitin-proteasome pathways and cancer cell metabolism. Ubiquitin-specific peptidase 13 (USP13) specifically deubiquitinates and thus upregulates ATP citrate lyase and oxoglutarate dehydrogenase that drive ovarian cancer metabolism. These findings may lead to the development of USP13 inhibitors and new-targeted therapies in ovarian cancers.